2008
DOI: 10.2108/zsj.25.1075
|View full text |Cite
|
Sign up to set email alerts
|

Development and Growth of the Feather Star Oxycomanthus japonicus to Sexual Maturity

Abstract: Crinoids, including feather stars, are the most basal group among extant echinoderm classes and share a basic body plan. In spite of their importance for evolutionary developmental study, information on the development of crinoids has been limited, because there are not many species whose spawning season is known, and artificial spawning is impossible. Therefore, it is not easy to obtain fertilized eggs of crinoids. We have observed the spawning and development of the feather star Oxycomanthus japonicus for 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…They are the only two species of crinoids in which eggs and larvae are reliably accessible annually and where useful data on their morphology and gene expression during development are available (Hara et al 2006;Holland 1991;Nakano et al 2003;Shibata et al 2008). The ancestral pattern of nervous system development in echinoderms is inferred from our data and suggestions on the early evolution of deuterostome life cycles put forward based on the basiepithelial nerve cells formed in M. rotundus doliolaria larvae.…”
Section: Introductionmentioning
confidence: 84%
“…They are the only two species of crinoids in which eggs and larvae are reliably accessible annually and where useful data on their morphology and gene expression during development are available (Hara et al 2006;Holland 1991;Nakano et al 2003;Shibata et al 2008). The ancestral pattern of nervous system development in echinoderms is inferred from our data and suggestions on the early evolution of deuterostome life cycles put forward based on the basiepithelial nerve cells formed in M. rotundus doliolaria larvae.…”
Section: Introductionmentioning
confidence: 84%
“…In comparison, feather stars are more accessible, since there are those that live in shallower waters. The feather star O. japonicus inhabits shallow rocky seashores around Japan, and can be collected by scuba divers near the Misaki Marine Biological Station (MMBS), the University of Tokyo, situated at the tip of the Miura Peninsula facing Sagami Bay, at around 5 m depth [52]. Such wild specimens are maintained in cages hung at a depth of 3 m in the cove of the MMBS.…”
Section: The Feather Star Oxycomanthus Japonicus Is a New Model Formentioning
confidence: 99%
“…These studies also used the specimens from the MMBS. Recently, Shibata et al reported that sexually mature females and males captured at MMBS spawn naturally on a neap-tide day in middle to late October [52]. Eggs and sperm were collected and fertilized eggs were reared into larvae, from which juveniles were obtained.…”
Section: O Japonicus As a Model Species For Developmental And Regenementioning
confidence: 99%
See 2 more Smart Citations